Computational approaches to the prediction of the redox potentials of iron and copper bioinorganic systems. Issue 22 (30th August 2016) - Bruschi, Maurizio; Breglia, Raffaella; Arrigoni, Federica; Fantucci, Piercarlo; De Gioia, Luca
Abstract: Aim of this contribution is to review some recent quantum mechanical approaches used to compute the redox potentials of transition metal complexes, with the emphasis on copper and iron species, which are particularly relevant in inorganic biochemistry and in synthetic chemistry of bio‐mimetic compounds. The paper presents also new DFT results obtained on Cu and Fe aquo ions in the framework of the Thermodynamic Integration and Grand Canonical Ensemble approaches. Such results show that without explicit inclusion of water molecules in the external solvation shells (even using a continuum solvation model) also very advanced methodologies fail to predict the redox potential in an acceptable manner. This is a confirmation of some previous studies which however never addressed this specific problem along the aforementioned approaches. Better results are obtained, on the contrary, on a series of Cu(II) complexes with Gly, Ala, en, Im, and water ligands with coordination type N 2 O 2 or N4 . In this case, the complexes are surrounded by nine water molecules which may partially alleviate the inadequacy of the continuum solvent models, especially in the case of highly positively charged species. Abstract : Calculations of the redox potential of copper complexes, in particular in aqueous solution, are difficult due to the significant structural rearrangements that often accompany the reduction from Cu(II) to Cu(I) complexes and the specific interactions between water molecules and metal complexes. MD‐based approaches, such as thermodynamic integration and the grand canonical ensemble method with explicit solvent representation, partly alleviate the inadequacies of methods based on single calculations of the species using implicit solvent models.